Novel EP4 Receptor Agonist‐Bisphosphonate Conjugate Drug (C1) Promotes Bone Formation and Improves Vertebral Mechanical Properties in the Ovariectomized Rat Model of Postmenopausal Bone Loss. (April 2015) - Liu, Careesa C; Hu, Sally; Chen, Gang; Georgiou, John; Arns, Steve; Kumar, Nag S; Young, Robert N; Grynpas, Marc D
ABSTRACT: Current treatments for postmenopausal osteoporosis aim to either promote bone formation or inhibit bone resorption. The C1 conjugate drug represents a new treatment approach by chemically linking the antiresorptive compound alendronate (ALN) with the anabolic agent prostanoid EP4 receptor agonist (EP4a) through a linker molecule (LK) to form a conjugate compound. This enables the bone‐targeting ability of ALN to deliver EP4a to bone sites and mitigate the systemic side effects of EP4a, while also facilitating dual antiresorptive and anabolic effects. In vivo hydrolysis is required to release the EP4a and ALN components for pharmacological activity. Our study investigated the in vivo efficacy of this drug in treating established bone loss using an ovariectomized (OVX) rat model of postmenopausal osteopenia. In a curative experiment, 3‐month‐old female Sprague‐Dawley rats were OVX, allowed to lose bone for 7 weeks, then treated for 6 weeks. Treatment groups consisted of C1 conjugate at low and high doses, vehicle‐treated OVX and sham, prostaglandin E2 (PGE2 ), and mixture of unconjugated ALN‐LK and EP4a to assess the effect of conjugation. Results showed that weekly administration of C1 conjugate dose‐dependently increased bone volume in trabecular bone, which partially or completely reversed OVX‐induced bone loss in the lumbar vertebra and improved vertebral mechanical strength. The conjugate also dose‐dependently stimulated endocortical woven bone formation and intracortical resorption in cortical bone, with high‐dose treatment increasing the mechanical strength but compromising the material properties. Conjugation between the EP4a and ALN‐LK components was crucial to the drug's anabolic efficacy. To our knowledge, the C1 conjugate represents the first time that a combined therapy using an anabolic agent and the antiresorptive compound ALN has shown significant anabolic effects which reversed established osteopenia. © 2014 American Society for Bone and Mineral Research.